Techno-Economic Analysis of Gas Turbine Compressor Washing to Combat Fouling - Abass, Kabir Oliade (Cranfield University, 2015)
Among the major deterioration problems a gas turbine encountered while in operation is compressor blade fouling. This is the accumulation and adhesion of dirt and sediment on the compressor blade which contributes between 70 to 85% of gas turbine performance loss. Fouling reduces turbine air mass flow capacity, compressor pressure ratio and overall gas turbine efficiency. In most cases, its effect does not manifest immediately in gas turbine power output and efficiency since they are not measured directly. However, it is apparent on the gradual increase in Turbine Entry temperature (TET) and Exhaust Gas Temperature (EGT). More fuel is burnt in the combustion chamber to maintain turbine power output which leads to high combustion flame temperature and thus reduces creep life of hot components. This research seeks to analyse the technical and economic consequences of compressor fouling in overall gas turbine performance. The work begins with simulation of TS3000 engine and examination of its design and off design performance. Subsequently, medium size gas turbine engine was modelled, simulated and its performance at different condition was examined to validate the outcome of field data analysis. Three months field operating data of Hitachi H-25 gas turbine generator used for power generation at bonny oil and gas terminal in Nigeria was collected and corrected to international standard ambient condition, using thermodynamic calculations. These data were analysed to determine the effect of fouling on the engine fuel consumption, power output in order to determine the plant profitability. The above analysis gives an estimation of fuel cost saving benefit of $41,000 over the period of one year plant operation due to regular two weekly compressor online water wash which is a good indication of the engine efficiency.
Keywords: Compressor Fouling; Thermodynamic condition; Degradation; ISO; Turbine Entry Temperature